A rare cause of recurrent abdominal pain: Three familial cases with hereditary angioedema - Dertlioglu, Selma B.; Cicek, Demet; Yesilova, Yavuz (Medknow Publications & Media Pvt Ltd, 2013)
[Abstract Not Available]
Keywords: C1 Inhibitor Deficiency; Management; Consensus